Benralizumab for adults with rare and off-label eosinophilic disorders: a 52-week prospective, single-center study - Talmon, Aviv; Shamriz, Oded; Rubin, Limor; Ribak, Yaarit; Aynor, Iris; Nevo, Adam; Elia, Anna; Sion, Meitav Ben; Forkosh, Esther; Hershko, Alon Y.; Tal, Yuval (Frontiers in Immunology, 2025)
BackgroundRare eosinophilic disorders are challenging to manage due to their heterogeneity and lack of targeted therapies. Benralizumab, an anti-IL-5 receptor monoclonal antibody approved for the treatment of severe eosinophilic asthma and eosinophilic granulomatosis with polyangiitis (EGPA), has not been systematically studied in other eosinophilic conditions.ObjectiveTo assess the efficacy and safety of benralizumab in adults with rare, non-asthmatic eosinophilic disorders over 52 weeks.MethodsIn this single-center, prospective, open-label study, 17 adults with diverse eosinophilic diseases received benralizumab 30 mg every 4 weeks for 24 weeks; responders continued up to 52 weeks. The primary endpoint was ≥50% reduction in peripheral eosinophil counts or tissue infiltration. Secondary outcomes included symptom improvement, reduced exacerbations, corticosteroid withdrawal, and safety.ResultsOf the 19 enrolled patients, 17 initiated treatment. Sixteen achieved clinical resolution, and all showed complete peripheral eosinophil depletion. Corticosteroids were discontinued in all completers. One patient had a partial response, and one discontinued due to mild, unrelated liver enzyme elevation. No serious adverse events occurred. Relapses were observed after treatment cessation. Efficacy was demonstrated across heterogeneous conditions, including eosinophilic leukemia, folliculitis, vaginitis, and IgG4-related disease.ConclusionBenralizumab is safe, well-tolerated, and effective in diverse rare eosinophilic disorders, enabling corticosteroid discontinuation and symptom control. These findings support its broader therapeutic potential and warrant further investigation.